Tool Path Planning for Five-Axis End Milling of Cycloidal Gears and Its Full Tooth Profile Accuracy Measurement - WANG, Jian; LIAO, Longxing; LUO, Shanming; MO, Jingyu (Engineering Transactions, 2023)
This paper proposes a method of end milling of cycloidal gears using a five-axis computer analytical control (CNC) machine tool. Firstly, the basic principle of the five-axis end milling of cycloidal gears is introduced. The cutting characteristics of the ball-end and the flat-end cutters are analyzed. Secondly, the path planning method of the five-axis end milling of cycloidal gears is researched. A curvature matching method is used to check for local over-cut interference and a minimum distance method is used to check for global collision interference. These two interferences are avoided by calculating the feasible range of cutter orientations and adjusting the dips of cutter shafts. Tests of end milling of cycloidal gears are carried out using a ball-end cutter and a flat-end cutter, respectively. Finally, full tooth profile accuracy measurements are undertaken with an image-measuring instrument to assess the quality of cycloidal gears processed in this way. This study provides a theoretical basis for the improvement of the tooth profile accuracy and surface quality of cycloidal gears.